Analysis on Corrosion Failure of Copper Tubes of Hydroelectric Generator Oil - Cooler - WANG Li-ge, CHEN Xin, WANG En-ze (Cailiao Baohu)
Corrosion perforation failure occurred on copper tubes of hydroelectric generator oil-cooler during the service period. Combined with the working conditions, micromorphology, chemical composition and structure of the corroded copper tubes were analyzed by SEM, XRD, EDS and metallurgical microscope. Results showed that the poor working conditions of the hydropower plant caused sediment and microbial deposition, which led to the under-deposit corrosion of copper pipes. The excessive concentration of Cl- in the water quality promoted tubes corrosion further.